Šuchov's bent networks: The impact of network curvature on Šuchov's gridshell designs. (February 2021) - Schling, Eike; Barthel, Rainer
Graphical abstract: Highlights: Using theories of differential geometry to analyse the curvature and bending of elastic gridshells. Systematic analysis and interpretation of four structural typologies by Vladimir Šuchov. Deduction of fundamental design and construction strategies based on prefabricated and installed states. Impact of elastic steel construction on gridshell design. Abstract: At the turn of the twentieth century, the Russian engineer Vladimir Šuchov developed an internationally acclaimed design language for steel construction. His filigree constructions – from lattice shell to the hanging roof – are timeless in their economy, lightness and, not least, simplicity. By combining a profound geometric and mechanical knowledge, Šuchov succeeded in deducing astonishingly pragmatic designs. A decisive strategy for simplification was the deliberate, elastic and plastic deformation of Z, L and flat steel profiles into continuously curved structural elements. As a result, Šuchov was able to assemble complex doubly curved grids using only repetitive components and simple riveted connections. In this paper we conduct a geometrical analysis of these structures looking at the curvature behaviour of four exemplary structures with increasing complexity: the hyperbolic tower, the rotational hanging roof, the cylindrical lattice vault, and the parabolic, double-curved gridshell. By systematically deriving their geometry and examining the three axes of curvature of each rod within those grids, we discover previously undescribed deformations of the steel members and deduce their associated bending moments and stresses. The results reveal Šuchov's systematic approach to utilizing elastic deformation to simplify construction, and offer conclusions about the prefabrication, the construction process, and the design approach he used for his lattice constructions. This has a direct impact not only on specific repair measures and structural analysis of his structures, but also on current research and the design and construction of similar gridshells today.